Role of ARX Gene in Infantile Spasms and Dystonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The role of ARX gene in a syndrome of infantile spasms with generalized dystonia was investigated in 6 boys from 4 families at the University of Florence, Italy, and other centers in Italy, Japan, and USA.